Acoustic performance of contemporary public libraries: an evaluation of public libraries in Melbourne, Australia. (4th March 2017) - Rajagopalan, Priyadarsini; Nguyen, Hoang Thuy Ha; Carre, Andrew
ABSTRACT: Contemporary public libraries play an important role in modern society providing a wide range of community services in addition to the traditional function of affording access to written art and information. Libraries have experienced increasing usage as they have developed into multipurpose facilities, adapting to changes in technology and society. Despite these changes, study and reading areas with good acoustic conditions have remained important for concentrated learning and work. This study investigates the acoustic conditions of seven public libraries in metropolitan Melbourne using objective measurements. Reverberation time measurements were undertaken in the State Library of Victoria which has the highest number of users of the libraries considered. The results showed that the noise levels under operating conditions were generally higher than expected. The reverberation time was high and other measures such as speech intelligibility were poor. Even though some noise management strategies were being employed to enhance acoustic conditions, indoor noise levels in contemporary public libraries are concerning. Noise generated from footsteps on hardwood floors, people talking, equipment operation and noise from traffic were the main sources of noise observed. Recommendations for improving acoustic conditions include application of absorptive materials for the floors and walls and appropriate noise insulation for façades.